PENGARUH METODE PEMBELAJARAN EKONOMI KREATIF TERHADAP MINAT BELAJAR SISWA DI MTS MOHAMAD HEKAL - Natasya Karlia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of creative economy learning methods on students’ learning interest at Mts Mohamad Hekal. The research employed a quantitative approach with a quasi-experimental design. The sample was selected using purposive sampling techniques, focusing on classes considered ready to receive creative economy–based learning. Data collection techniques included questionnaires, observations, and documentation. The questionnaire instrument was used to measure students’ learning interest before and after the implementation of the creative economy learning method. This learning method was applied through brainstorming activities, project-based creative production, and simple economic simulations that actively involved students in the learning process. The results showed that the implementation of creative economy learning methods had a positive effect on students’ learning interest. Improvements were found in students’ enthusiasm, attention, enjoyment, and participation during classroom activities. In addition, students became more active in discussions, teamwork, and expressing their opinions. Creativity-based learning also helped students understand the material more concretely and meaningfully through direct experience. Therefore, the creative economy learning method can be used as an effective alternative learning strategy to improve students’ learning interest in Islamic-based schools.